Risiko Gagal Ginjal Akut Pasca Bedah Jantung yang memerlukan Terapi Pengganti Ginjal Kontinyu - Juweni Joe; Zuswahyuda Samsu; April Retno; Rita Zahara; Ronggo Prakoso; Ardiyan A (Jurnal Kardiologi Indonesia, 2013)
Background: Acute renal failure is a rare but serious complication followingcardiac surgery and associated with increased mortality and morbidity.Objective:To identify factors associated with mortality and mortality ofpatients with acute renal failure after cardiac surgery treated with continuousrenal replacement therapy.Method: This was a cohort retrospective study on cardiac surgery patientswho developed acute renal failure requiring renal replacement therapy aftersurgery in Harapan Kita National Cardiac Center between January 2011and April 2012. Data was retrieved from medical record and consistedof pre-operative, intra-operative, and post-operative variables. Risk factoridentification was done using multivariate logistic regression analysis,whereas relative risk analysis was applied to know the association betweenrisk factor and morbidity. Direct or indirect effect of variables on renal failurewas analyzed using Barttlet’s and anti-image correlation test.Results: A total of 110 cases were obtained during the study period; 70(63.3%) among them were men. Patients mean age was 57.6 years. Preoperativerenal failure, New York Heart Association Functional ClassificationClass (NYHA) class IV, critical condition, coronary revascularization surgeryand bleeding, post-operative anemia, bleeding and venous saturation <65%showed a trend of mortality and morbidity rate between 0.1 and 9.1. TheKeiser-Meyer-Olkin (KMO) value and Barttlet’s test showed that re-surgery,bleeding and low inotropic score resulted in 31.63% probability of havingpost-operative renal failure.Conclusion: Re-surgery, bleeding and inotropic use may result in postoperativerenal failure.